Magnetization transfer ratio: a quantitative imaging biomarker for 5q spinal muscular atrophy - Hayes, Jennifer; Keßler, Tobias; Sam, Georges; Hayes, J. M.; Lentz, S. I.; Heiland, Sabine; Bendszus, Martin; Wick, Wolfgang; Weiler, Markus (European journal of neurology, 2021)
In this exploratory study, we used magnetization transfer contrast (MTC) imaging, an MRI technique that provides information about protons bound to macromolecular structures such as myelin lipids or ...
First published: 12 September 2020
Gesehen am 13.12.2021